Regulated multi-sited practice for physicians in China: incentives and barriers - Lihui Xu; Min Zhang (Global Health Journal, 2018)
The multi-sited practice (MSP) policy in China is expected to exert found implications upon uneven distribution of high-quality medical resources, coupled with the widespread phenomenon of physician’s informal practices on multiple sites. Since 2009, the Chinese government has upheld a policy that allows medical doctors to take on secondary jobs for the purpose of encouraging talented physicians to work in medical institutions and underdeveloped areas where their expertise is badly needed. This paper focuses on the MSP policy in China by examining how it has been implemented at the national and provincial levels through a review of government documents, statistical information, academic papers, and newspaper accounts. Despite the MSP policy is to offer incentive to physicians at first-tier public hospitals to work in primary care centers or areas where their expertise, the evidence is hard to find. This paper identifies several outstanding challenges to the MSP policy : (1) The importance of the MSP policy which is made by the central government is perceived differently at the provincial level by health officials and hospital administrators; (2) Interest in implementing the policy varies among physicians and hospitals; (3) Concerns about quality control and legal responsibilities for medical doctors to take on secondary jobs are widespread. China’s MSP policy differs from the “dual practice” policy in many countries because of its top-down approach, with its emphasis on government’s role and administrative intervention. This paper’s findings may be useful for other developing countries where medical expertise is unevenly distributed due to market forces. On the special occasion of the Alma Ata Declaration’s 40th anniversary and for the sake of promoting Universal Health Coverage, this paper also aims at sharing with other countries China’s experience in trying to develop an adequate force of primary care professionals. At the end of this paper, a four-point proposal is made for policy makers in China.